Pengembangan Modul Pembelajaran Pendidikan Pancasila Berbasis Problem Based Learning (PBL) untuk Meningkatkan Motivasi Belajar dan Tanggung Jawab Siswa SD N Transad - Erpita, Rosi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to develop a Problem Based Learning (PBL)-based Civic Education learning module that can improve students’ learning motivation and responsibility at SD Negeri Transad. The method used is Research and Development (R&D) with the 4D development model (Define, Design, Develop, and Disseminate). The research subjects were fifth-grade students of SD Negeri Transad, with data collection instruments including expert validation questionnaires, learning motivation questionnaires, and student responsibility observations. The results showed that the PBL-based module developed was categorized as “highly feasible” based on assessments from material experts and media experts. Field trials also indicated that the use of the module could significantly enhance students’ learning motivation and foster a sense of responsibility in the learning process. In conclusion, the PBL-based learning module is feasible to be used as Civic Education teaching material in elementary schools as it can foster active, responsible, and motivated students. Keywords: Civic Education, elementary school, learning motivation, learning module, Problem Based Learning, responsibility